Communication Systems and Community Leadership: Study Rural Community of the Ibu Kota Nusantara - Mahayasa, I Gede Aryana (Manajemen dan Bisnis, 2023)
This study aims to explore and identify the communication and leadership system of the rural community where the Ibu Kota Nusantara is located in the transformation project to become the capital of the archipelago and a smart city. This research is qualitative research with a descriptive approach. The sample and respondents of the study were community and traditional leaders as well as religious leaders in the area closest to the location of the Ibu Kota Nusantara with a total of 113 respondents. The results showed that most of the people in the villages located in the capital city of the archipelago felt that the communication system implemented by the government in the context of the process of moving the country's capital was still lacking. The community also feels that the leadership of the central and local governments is also very lacking. The community hopes to be invited to play an active role in all preparations for the relocation of the state capital. The community hopes to be able to become development actors, have the competence to participate in developing their region, and in the end can enjoy the results of the development, with the increase in the economy and the standard of living of the community.